Functional magnetic resonance imaging of human prefrontal cortex activation during a spatial working memory task. - McCarthy, G; Blamire, A; Puce, A; Nobre, A; Bloch, G; Hyder, F; Goldman-Rakic, P; Shulman, R (1994)
High-speed magnetic resonance (MR) imaging was used to detect activation in the human prefrontal cortex induced by a spatial working memory task modeled on those used to elucidate neuronal circuits in nonhuman primates. Subjects were required to judge whether the location occupied by the current stimulus had been occupied previously over a sequence of 14 or 15 stimuli presented in various locations. Control tasks were similar in all essential respects, except that the subject's task was to detect when one of the stimuli presented was colored red (color detection) or when a dot briefly appeared within the stimulus (dot detection). In all tasks, two to three target events occurred randomly. The MR signal increased in an area of the middle frontal gyrus corresponding to Brodmann's area 46 in all eight subjects performing the spatial working memory task. Right hemisphere activation was greater and more consistent than left. The MR signal change occurred within 6-9 sec of task onset and declined within a similar period after task completion. An increase in MR signal was also noted in the control tasks, but the magnitude of change was less than that recorded in the working memory task. These differences were replicated when testing was repeated in five of the original subjects. The localization of spatial working memory function in humans to a circumscribed area of the middle frontal gyrus supports the compartmentalization of working memory functions in the human prefrontal cortex and the localization of spatial memory processes to comparable areas in humans and nonhuman primates.